Um estudo sobre sistemas baseados em regras Fuzzy - Silva, André Luigi da (2020)
The practice of medicine is an analytical and uninterrupted decision-making process in which the variables involved are often subjective (i.e. not measurable) so Fuzzy Logic is a very participative resource in the decision-making process. Within this scenario, this research aims to conduct a study of concepts that use the Fuzzy Theory and suggests a model that measures the activity of an inflammatory bowel disease. Crohn’s disease, among other indexes, has an activity meter known as the Harvey-Bradshaw index for which a fuzzy model will be proposed and relate the accentuation of symptoms to the stage of the disease.